Work performance assessment in Thai homeless shelters: An exploratory factor analysis - Thanapet, Uthaikan; Ammawat, Watthanaree; Rueankam, Maliwan; Chatthong, Winai; Khemthong, Supalak (Journal of Associated Medical Sciences, 2025)
Background: Institutional sheltering can lead to occupational deprivation and psychosocial disengagement, particularly among adults with mental health-related disabilities. In Thailand, homeless shelters operate under rigid custodial systems that may hinder functional recovery, highlighting the need for culturally adapted assessment tools. Objectives: To validate an adapted version of the Assessment of Work Performance (AWP) for use in Thai homeless shelters and to identify functional skill patterns and psychosocial barriers that inform allied health service planning. Materials and methods: A cross-sectional study was conducted with 60 adults with mental health–related disabilities residing in a government-operated destitute shelter. Participants completed a work-based AWP task rated across seven subskills. Exploratory factor analysis (EFA) examined the underlying factor structure, while regression analysis tested the predictive value of extracted factors on occupational performance. Results: The EFA supported a two-factor solution; 1) task adaptation and relational organization, and 2) communication and expression-accounting for 56.78% of the total variance (KMO=0.696, Bartlett’s test significant). Regression analysis showed that task adaptation and relational organization significantly predicted occupational performance, explaining 69.6% of the variance (R²=0.696). Conclusion: Task adaptation and environmental structuring are key determinants of occupational engagement in institutional shelter settings. Performance-based assessment, combined with structured observation during task engagement, provides a culturally relevant strategy for allied health professionals to guide individualized rehabilitation for marginalized populations in Thai homeless shelters.